Identification of Mexican maize races adapted to moisture deficient conditions using biogeographical data - Ruiz Corral José Ariel; Sánchez González José de Jesús; Hernández Casillas Juan Manuel; Willcox, Martha C.; Ramírez Ojeda Gabriela; Ramírez Díaz José Luis; González Eguiarte Diego Raymundo (Revista Mexicana de Ciencias Agrícolas, 2018)
We worked with a database of recent accessions of 54 races of maize from Mexico, whose passport details were extracted from the Genetic Resource Unit from INIFAP ́s Germplasm Bank. From the geographical coordinates of the accessions, was made an accession characterization by site, conditions of moisture availability for the period from May to October for the development of maize, based on the environmental information system from INIFAP and the IDRISI Andes system. With these data, a statistical analysis was made that included an analysis of variance and analysis of numerical taxonomy (cluster analysis) with the product moment correlation between races. Additionally was performed an accessions analysis by race to identify the accessions that developed under moisture-deficient environments. Accessions were selected with adaptation to an environment with humidity index (IH) (precipitation / potential evapotranspiration) from May to October less than 0.5. The results showed the identification of five racial groups, of which one of them stood out for its adaptation to an HI between 0.39 and 0.53. This group included Chapalote, Dulcillo Northwest, Tuxpeño Norteño, Conical Norteño, Tablilla of Ocho and Gordo races. Accessions analysis reported the presence of maize in a total of 677 sites with semi-arid conditions in the May-October season. The 677 accessions represent 24 races. These results suggest that in Mexico there are genetic resources, related to the races of maize, which could be useful in breeding programs aimed to maize adaptation to drought stress.